2015
DOI: 10.1186/s12883-015-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

Argentine tango in Parkinson disease – a systematic review and meta-analysis

Abstract: BackgroundParkinson’s Disease (PD) is a neurodegenerative disease with increasing motor and non-motor symptoms in advanced stages. In addition to conventional exercise therapy and drug treatment, Argentine Tango (AT) is discussed as an appropriate intervention for patients to improve physical functioning and health-related quality of life. This review aimed to summarize the current research results on the effectiveness of AT for individuals with PD.MethodsThe global literature search with the search terms “(Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 38 publications
7
82
0
3
Order By: Relevance
“…This average magnitude of change meets the threshold for established clinically important differences (minimum of 2.5 for UPDRS to 3.5 for MDS-UPDRS) with variation in reported meaningful differences due to instrument used (UPDRS vs. MDS-UPDRS) and severity of disease progression [66, 67]. The magnitude of effects of TCQ on Part III of the UPDRS that we observed are similar to those reported for physiotherapy [68], but lower than those reported following training in Argentine Tango [69], or for patients taking dopamine medications [57] or undergoing deep brain stimulation [70]. …”
Section: Discussionsupporting
confidence: 67%
“…This average magnitude of change meets the threshold for established clinically important differences (minimum of 2.5 for UPDRS to 3.5 for MDS-UPDRS) with variation in reported meaningful differences due to instrument used (UPDRS vs. MDS-UPDRS) and severity of disease progression [66, 67]. The magnitude of effects of TCQ on Part III of the UPDRS that we observed are similar to those reported for physiotherapy [68], but lower than those reported following training in Argentine Tango [69], or for patients taking dopamine medications [57] or undergoing deep brain stimulation [70]. …”
Section: Discussionsupporting
confidence: 67%
“…7,[18][19][20][21] In particular, dance styles that induce frequent movement cessation and initiation and backwards steps, such as tango seem to induce greater improvements in motor outcomes in PD. 22,23 This is particularly important since backwards walking is challenging for people with PD because it disturbs balance and could trigger freezing events. 24 Several studies have shown altered biomechanical responses during compensatory backward stepping in people with PD compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, effective programs are an Intensive Rehabilitation Program (4 weeks, 5 times a week, combined types of exercise) [78,79], and the Lee Silverman Voice Treatment -BIG program (high amplitude movements, sensory recalibration and self-cueing) [80]. Other types of exercise for which evidence is increasing are Tai Chi [81][82][83], hydrotherapy [84], boxing [85] and dancing [86][87][88]. There is very little evidence for exercise to improve hand function.…”
Section: Exercisementioning
confidence: 99%